Development of a single‐cell X‐ray fluorescence flow cytometer. (16th June 2016) - Crawford, Andrew M.; Kurecka, Patrick; Yim, Tsz Kwan; Kozemchak, Claire; Deb, Aniruddha; Dostál, Lubomír; Sun, Cheng-Jun; Brewe, Dale L.; Barrea, Raul; Penner-Hahn, James E.
Abstract : An X‐ray fluorescence flow cytometer capable of performing single‐cell metal analysis is described and developed. This device is capable of detecting m M to µ M concentrations from sample volumes as small as ∼50 fL. Abstract : An X‐ray fluorescence flow cytometer that can determine the total metal content of single cells has been developed. Capillary action or pressure was used to load cells into hydrophilic or hydrophobic capillaries, respectively. Once loaded, the cells were transported at a fixed vertical velocity past a focused X‐ray beam. X‐ray fluorescence was then used to determine the mass of metal in each cell. By making single‐cell measurements, the population heterogeneity for metals in the µ M to m M concentration range on fL sample volumes can be directly measured, a measurement that is difficult using most analytical methods. This approach has been used to determine the metal composition of 936 individual bovine red blood cells (bRBC), 31 individual 3T3 mouse fibroblasts (NIH3T3) and 18 Saccharomyces cerevisiae (yeast) cells with an average measurement frequency of ∼4 cells min −1 . These data show evidence for surprisingly broad metal distributions. Details of the device design, data analysis and opportunities for further sensitivity improvement are described.